Mask, transformation and identity in the Andes / Gisela Cánepa Koch, Fondo Editorial de la Pontificia Universidad Católica, Lima, 1998. 349 pp. Ilustraciones. - Huerta-Mercado, Alex (1998)
The review does not present a summary.